Evaluation of Different Antenna Positions for Joint Radar-Communication at 77 GHz - Lübke, Maximilian; Fuchs, Jonas; Dubey, Anand; Frank, Martin; Weigel, Robert; Lurz, Fabian (Kleinheubacher Tagung 2021, 2021)
The development of millimeter wave systems is driven by the strong trend towards the new communication generations and especially by the emerging joint radar and communication design approach. Safety critical applications like platooning or intersection assistance will significantly benefit from the combination of sensing and communication. This combination requires that both operate on the same frequency bands either in a co-design, a cooperation or even in a coexistence, using the same hardware. However, each technology has its own requirements. While radar performs a channel measurement and thus, needs a wide field of view, communication aims to minimize the interference for other not addressed receivers (e. g. in a platoon) by a focused antenna design. The proposed work analyses the effect of antenna positioning and antenna characteristics (omnidirectional and focused) for a typical automotive scene by evaluating both the communication and sensing performance. Especially, the positions at the front bumper – typical for radar sensors– and at the left mirror convinced regarding the vehicular communication as well as the sensing behaviour. <br